(untitled) (Eduscotech, 2022)
This study aims to describe the implementation of Adaptive Physical Education (APE) learning for deaf students at Panca Bhakti Special Needs School in Magetan Regency, as well as to identify the supporting factors, obstacles, and teacher strategies in optimizing the learning process. This research employed a descriptive qualitative approach. Data were collected through classroom observations, in-depth interviews, and documentation involving physical education teachers, special assistant teachers, school principals, and deaf students as research participants. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings reveal that Adaptive Physical Education learning was implemented based on the principles of inclusivity, modification, and individualization. The learning process emphasized visual communication strategies, including the use of sign language, movement demonstrations, visual media, and nonverbal expressions to facilitate students’ understanding. Learning evaluation focused primarily on student participation, motor skill development, and individual progress rather than standardized performance outcomes. Supporting factors in the implementation of APE included positive teacher attitudes, strong support from the school and parents, and high levels of student motivation. However, several inhibiting factors were identified, such as limited availability of adaptive learning resources, insufficient teacher training related to adaptive physical education, and a lack of technology-based learning media. In conclusion, the implementation of adaptive physical education based on visual communication strategies contributed positively to improving participation, motor skills, and self-confidence among deaf students. These findings highlight the importance of teacher preparedness, adequate resources, and visual-based instructional approaches in optimizing adaptive physical education learning for students with hearing impairments.